The new Whole30 : the definitive plan to transform your health, habits, and relationship with food - Urban, Melissa (Rodale, 2024)
"Since it's evolution in 2009, the Whole30 program has helped millions of people lose weight and successfully transform their health in just 30 days. Through the years though, the Whole30 philosophy has been modified and improved upon as the nutritional landscape has changed. In The Essential Whole30, co-creater of the plan Melissa Urban has revised the original program and created new recipes to help more readers than ever reduce inflammation, rebalance hormones, control cravings and break unhealthy eating patterns to find food freedom. The upgrades to the original program will include new food freedom rules that have been refined over the years based on current science and the everchanging food landscape, as well as 100 all-new recipes: 50 Whole30 recipes, 50 plant-based. The book will also include a new Plant-Based Whole30 program, which launched in 2022, after years of research, planning and beta testing. This book will be the ultimate guide, rendering the original book obsolete, with straightforward instructions on how to start and stick to the program to achieve the best results. With no-nonsense tips, Melissa establishes the revised, essential foundation for planning, preparing, and cooking delicious meals to curb cravings, lose weight and be healthy. It is sure to be the health bible for the millions of Whole30 enthusiasts, as well as those who are new to the popular plan"--